Pengajaran dan pembelajaran: pembinaan modul pembelajaran reka bentuk struktur kayu Secara interaktif - Mohammed Sani, Abdul Rahim (2003)
The growth of information technologies in the fields of education is undeniable, nowadays. The increasing needs in the learning and teaching systems require of those involved to pay their greatest attentions to the subjects taught to achieve the objectives, aims and goals. For this purpose the Multimedia Interactive Module (MMI) is developed to support or in helping to accommodate the students in the Wood Design subjects. There were about 38 students undertaking the Degree Of Civil Engineering (Wood Bases) at Kolej Universiti Teknologi Tun Hussein Onn (KUiTTHO) who were involved as the respondents. Descriptive statistics were used in collecting and analyzing data's. In a nutshell, or overall, based on the results of the researches conducted, it may be concluded that the researches made showed that the congregation of the students were giving positive responds towards the MMI. All respondent agree that MMI is friendly user. It shown by score of the min, which are 3.22. For display qualities, 2.70 were shown by score of the min. It's mean, all respondent doesn't agree with the quality. For motivation and cognitive aspect, respondent gave 3.17. Apart from that, it is also found that the majority of the students were more interested towards multi-kinds of means or mediums usage than the ordinary methods used, for instance, texts, audios and visuals. Nevertheless there are some particular aspects that needed to be given more attention for their improvements in order to strengthen the MMI